Critical current anisotropy of GdBCO tapes grown on ISD–MgO buffered substrate. (23rd October 2015) - Lao, M; Bernardi, J; Bauer, M; Eisterer, M
Abstract: The critical current anisotropy of a GdBa2 Cu3 O7 (GdBCO) coated conductor (CC) was investigated. The MgO buffer layer was grown by the inclined substrate deposition (ISD) technique leading to a tilted c -axis growth of the GdBCO layer by 24° from the tape normal. The J c was measured in two current directions: longitudinal and transverse to the tape. The self-field J c in the 2 μ m thick GdBCO layer was 1.3 MA cm −2 and 0.88 MA cm −2 at 77 K in the longitudinal and transverse directions, respectively. The 30% lower value in the transverse direction results from the current flow across the weakly superconducting layer of GdBCO. The peak in the J c -anisotropy corresponding to intrinsic pinning appears at 24° with respect to the tape surface in the longitudinal direction and the anisotropy was highly asymmetric in a wide range of fields. Due to the large crystallographic tilt of the GdBCO with respect to the tape axes, a minimum caused by vortex channeling occurred in the transverse current direction which was observed for the first time at 77 K. Another consequence of the large crystallographic tilt angle is a pronounced competing effect of the crystallographic anisotropy and Lorentz force on J c in the variable Lorentz force configuration.